(3Jbhje GdCHOGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb aShi hGYed dCNQJc Jdb KhGHg ZOkG hdG jJe Pdc EdG HGdUMI hEf cGf JgHjQ GdUMI hEfeG jWdH ddJecf ef GdYde hGdYed s
(3BNQgG (B:s
(3hEf cGf ai COhjI GdeQcH eG jVYa bhJg Gda ef cKjQ abO LYd ef gPG Gf Gdbi GdOhGA GdcKjQ GdeaQO ai GdeQcH aGddg GdgGOi ddUhGH s
(3HgG LOGhds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
Keywords: (3GdWHs